Performance Degradation of Dye-Sensitized Solar Cells Induced by Electrolytes - Ru-Yuan Yang; Huang-Yu Chen; Fu-Der Lai (Advances in Materials Science and Engineering)
We investigated the change of the electric characteristics in dye-sensitized solar cell (DSSC) when the electrolyte has been injected and measured initially and lately for a period of time. It was found that the short-circuit current density decreased from 9.799 mA/cm2 to 7.056 mA/cm2 and the fill factor increased from 0.406 to 0.559 when the cell had stood for an hour, while the open-circuit photovoltage did not change due to fixed difference between the Fermi level of TiO2 and the oxidation-reduction potential of electrolyte. The results can be explained by using the variation of the series resistance in the equivalent circuit of the DSSC.